Span of Management: Theory and Practice - بعيرة ابوبكر (Dirasat in Economics and Business, 1976)
The span of management (som) is one of the classical organizational principles which the early management theorists advocated as early as the beginning of this century. For example, Henri Fayol, the father of contemporary management theory wrote about SOM in 191 8: «Whatever his rank. a man has only to command a very small number of direct subordinates, usually less than six, except that a foreman, who is dealing with quite a simpe operation, is in direct command of 20 or 30 men.»